2022
DOI: 10.1073/pnas.2202394119
|View full text |Cite
|
Sign up to set email alerts
|

Sleep facilitates spatial memory but not navigation using the Minecraft Memory and Navigation task

Abstract: Sleep facilitates hippocampal-dependent memories, supporting the acquisition and maintenance of internal representation of spatial relations within an environment. In humans, however, findings have been mixed regarding sleep’s contribution to spatial memory and navigation, which may be due to task designs or outcome measurements. We developed the Minecraft Memory and Navigation (MMN) task for the purpose of disentangling how spatial memory accuracy and navigation change over time, and to study sleep’s independ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 53 publications
3
9
0
Order By: Relevance
“…Additionally, other studies have also shown that participants in the middle range of the cohort in terms of age had better cognitive performance at shorter and longer sleep durations than both younger and older participants 30 . Moreover, a recent study showed that in participants of a similar age to ours, sleep can facilitate performance on memory-based tasks but not spatial navigation performance 15 . Another study found sleep fragmentation to be associated with poorer wayfinding performance only in older participants but not in younger participants 7 .…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Additionally, other studies have also shown that participants in the middle range of the cohort in terms of age had better cognitive performance at shorter and longer sleep durations than both younger and older participants 30 . Moreover, a recent study showed that in participants of a similar age to ours, sleep can facilitate performance on memory-based tasks but not spatial navigation performance 15 . Another study found sleep fragmentation to be associated with poorer wayfinding performance only in older participants but not in younger participants 7 .…”
Section: Discussionsupporting
confidence: 64%
“…Experimental sleep deprivation studies have also shown that sleep deprivation results in poorer spatial navigation performance [10][11][12][13] , although other studies report no significant changes in spatial navigation performance following sleep deprivation 14,15 . A recent study from our team also reported a quadratic (Ushaped) association between self-reported sleep duration and virtual spatial navigation performance on SHQ, where mid-range sleep duration was associated with optimal performance 16 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These domains are naturally more difficult to control experimentally, but they have the added benefit of generalizing to everyday life (Yarkoni, 2022). In parallel, lab‐based studies examining the effects of sleep on memory should employ more naturalistic designs involving complex stimuli such as videos (e.g., Antony et al, 2021; J. Chen et al, 2016) or virtual‐reality‐like experiences (e.g., K. C. Simon et al, 2022). Altogether, research on how sleep reactivation supports complex memories is at an exciting juncture, and we hope this review has helped to frame its commonalities and guide its future developments.…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%
“…These domains are naturally more difficult to control experimentally, but they have the added benefit of generalizing to everyday life (Yarkoni, 2022). In parallel, lab-based studies examining the effects of sleep on memory should employ more naturalistic designs involving complex stimuli such as videos (e.g., Antony et al, 2021;Chen et al, 2016) or virtual-reality-like experiences (e.g., K. C. Simon et al, 2022). Altogether, research on how sleep reactivation supports complex memories is at an exciting juncture, and we hope this review has helped to frame its commonalities and guide its future developments.…”
Section: Future Directions and Concluding Remarksmentioning
confidence: 99%